EMPLOYING SUSTAINABILITY ACCOUNTING STANDARDS AS A MECHANISM TO IMPROVE THE PERFORMANCE OF COMPANIES: AN ANALYTICAL STUDY IN THE IRAQI NATIONAL INSURANCE COMPANY - Hadeel Mohammed Noaman (Galaxy International Interdisciplinary Research Journal, 2023)
The current study aims to employ sustainability accounting standards in its dimensions "financial inclusion and capacity, customer privacy and data security, management of the legal and regulatory environment, systemic risk management, integration of risk factors ESG in credit risk analysis" as a mechanism to improve the performance of companies in its dimensions "employee satisfaction, improving productivity, and growth" Accordingly, in order to detect the level of availability of study variables at the Iraqi National Insurance Company, the questionnaire tool was adopted as a measuring tool, and accordingly (73) form was distributed to the sample of workers within the company, and in order to clarify the results that the study seeks to clarify, a set of methods were used to ensure that the test of the applied side of the study, and perhaps the most famous of these methods are represented in the arithmetic average, Standard deviation, level of importance, Pearson’s correlation coefficient, and impact coefficients between internal variables according to the SMART program. PLS & SPSS.V.28), and accordingly, after showing the results of the study, it was found that there is an interest of the Iraqi National Insurance Company to enhance transparency by using sustainability accounting standards in increasing the level of transparency and responsibility in the company’s business, through sustainability reports, the company’s performance in the environmental, social and economic fields is clarified, and thus customers and shareholders can understand the efforts made and assess the overall impact of the company, and therefore the most important recommendations of the study are that the Iraqi National Insurance Company should Conduct an analytical study to assess the current state of the company in relation to sustainability. This includes identifying strengths and weaknesses and identifying areas that need improvement.